Project Based Learning Model in Class X.9 of SMA Negeri 1 Semarang - Ari Anisha Rachmawati Nyaman (Jurnal Seni Tari, 2025)
Project-based learning (PjBL) has been widely applied in science and technology education, but its use remains limited in the context of arts education, particularly dance education. This study aims to describe the implementation of the PjBL model in dance education in class X.9 at State Senior High School 1 Semarang. The study employs a qualitative method with a phenomenological approach to understand students' subjective experiences in the process of creating original dance pieces. Data was collected through observation, interviews, and documentation, and then analyzed using triangulation. The results of the study indicate that the implementation of the PjBL model takes place systematically through three stages: planning with the development of teaching modules, implementation by adapting the planning from the teaching modules, and evaluation conducted collaboratively by the teacher and students through class discussions or feedback sessions. Each stage facilitates active student participation, encourages collaborative problem-solving, and produces original dance works. This study confirms that PjBL is effective in enhancing students' creativity, independence, and critical thinking skills in art education. These findings contribute to the development of project-based art pedagogy practices at the secondary education level.